Islamization of Science Naquib Al-Attas's Perspective - Katni Katni; Fista Nurjanah; Wawan Yulianto; Nur Aisyah; Fais Farkhani; Elfy Kameiliya Rahmah (Assyfa Journal of Islamic Studies, 2025)
The advancement of Islamic science, which once dominated world civilization, was the culmination of the integration of the values ​​of the spirit of Islamic teachings with science and technology, although the journey faced significant challenges. According to al-Attas, the greatest challenge facing Muslims in the Islamization of Islamic Science was the knowledge disseminated throughout the Islamic world by Western civilization. The Islamization of knowledge means the Islamization or purification of Western scientific products that have been developed and used as a reference in the discourse on the development of the Islamic education system in order to obtain a science that is "specifically Islamic." Al-Attas defines knowledge as a meaning that comes into the soul along with the soul's arrival at meaning and produces desires and self-will. Al-Attas defines the meaning of education as a process of instilling something into the human being and then emphasizes that something instilled is knowledge, and the purpose of seeking this knowledge is contained in the concept of ta’dib. Meanwhile, the goal of Islamic education is to instill virtue in the "human self" as an individual and as part of society. Ideally, Naquib wants Islamic education to be able to produce universally good people (al-insan al-kamil).